Feasibility and clinical impact of sharing patient-reported symptom toxicities and performance status with clinical investigators during a phase 2 cancer treatment trial. (June 2016) - Basch, Ethan; Wood, William A; Schrag, Deborah; Sima, Camelia S; Shaw, Mary; Rogak, Lauren J; Kris, Mark G; Shouery, Marwan; Bennett, Antonia; Atkinson, Thomas; Pietanza, M Catherine
Background: Clinicians can miss up to half of patients' symptomatic toxicities in cancer clinical trials and routine practice. Although patient-reported outcome questionnaires have been developed to capture this information, it is unclear whether clinicians will make use of patient-reported outcomes to inform their own toxicity documentation, or to prompt symptom management activities. Methods: 44 lung cancer patients that participated in a phase 2 treatment trial self-reported 13 symptomatic toxicities derived from the National Cancer Institute's Common Terminology Criteria for Adverse Events and Karnofsky Performance Status via tablet computers in waiting areas immediately preceding scheduled visits. During visits, clinicians viewed patients' self-reported toxicity and performance status ratings on a computer interface and could agree or disagree/reassign grades ("shared" reporting). Agreement of clinicians with patient-reported grades was tabulated, and compared using weighted kappa statistics. Clinical actions in response to patient-reported severe (grade 3/4) toxicities were measured (e.g. treatment discontinuation, dose reduction, supportive medications). For comparison, 45 non-trial patients with lung cancer being treated in the same clinic by the same physicians were simultaneously enrolled in a parallel cohort study in which patients also self-reported toxicity grades but reports were not shared with clinicians ("non-shared" reporting). Results: Toxicities and performance status were reported by patients and reviewed by clinicians at (780/782) 99.7% of study visits in the phase 2 trial which used "shared" reporting. Clinicians agreed with patients 93% of the time with kappas 0.82–0.92. Clinical actions were taken in response to 67% of severe patient-reported toxicities. In the "non-shared" reporting comparison group, clinicians agreed with patients 56% of the time with kappas 0.04–0.48 (significantly worse than shared reporting for all symptoms), and clinical actions were taken in response to 44% of severe patient-reported toxicities. Conclusion: Clinicians will frequently agree with patient-reported symptoms and performance status, and will use this information to guide documentation and symptom management. (ClinicalTrials.gov: NCT00807573).